(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The development of communication culture skills among primary students in English language education is crucial for preparing them to thrive in today’s globalized world. This article explores the significance of fostering communication culture skills, which encompass linguistic proficiency, cultural awareness, critical thinking, and collaborative abilities. By integrating cultural competence into English language classes, educators create inclusive learning environments that promote empathy, tolerance, and respect for diversity. Activities that prioritize speaking and listening proficiency, critical thinking, problem-solving, and collaborative learning experiences empower primary students to communicate effectively and respectfully in English. Leveraging technology and multimedia resources enhances students’ learning experiences, stimulating curiosity and facilitating cross-cultural exploration. Ultimately, fostering communication culture skills equips primary students with the tools they need to succeed in an interconnected and culturally diverse society.